Повсякденне життя українських селян у 1950–1960-х рр. (історіографія проблеми) - Лисак, В. (Історіографічні дослідження в Україні, 2010)
Проаналізовано історіографію вивчення повсякденного життя українських селян у 1950–1960-х рр. Автор дійшов висновку, що протягом декількох десятиліть була створена солідна наукова база дослідження українського села. Роботам притаманна увага до соціально-економічних, політичних та культурних умов існування сільської спільноти. Між тим проблема життєвої практики селян залишається поза увагою дослідників. The historiography of researches of Ukrainian peasants daily life in 1950 - 1960’s has been analysed. The author arrives the conclusion that over several decades an important base of scientific research of the Ukrainian villages has been created. The studies pay attention to the socio-economic, political and cultural living conditions of rural communities. Meanwhile the problem of practices of the peasants’ life is still out of the researchers’ attention.